Immunological Responses to Transgene-Modified Neural Stem Cells After Transplantation - Wei, Naili; Sun, Zhenxing; Yu, Jimei; Jia, Yanfei; Zheng, Peiqi; Tang, Hailiang; Chen, Jian (Frontiers in Immunology, 2021)
Neural stem cell (NSC) therapy is a promising therapeutic strategy for stroke. Researchers have frequently carried out genetic modification or gene editing of stem cells to improve survival or therapeutic function. However, NSC transplantation carries the risk of immune rejection, and genetic modification or gene-editing might further increase this risk. For instance, recent studies have reported on manipulating the stem cell genome and transplantation via the insertion of an exogenous gene derived from magnetotactic bacteria. However, whether transgene-modified stem cells are capable of inducing immunological reactions has not been explored. Although NSCs rarely express the major histocompatibility complex (MHC), they can still cause some immunological issues. To investigate whether transgene-modified NSCs aggravate immunological responses, we detected the changes in peripheral immune organs and intracerebral astrocytes, glial cells, and MHC-I and MHC-II molecules after the injection of GFP-labeled or mms6-GFP-labeled NSCs in a rat model. Xenogeneic human embryonic kidney (HEK-293T) cells were grafted as a positive control group. Our results indicated that xenogeneic cell transplantation resulted in a strong peripheral splenic response, increased astrocytes, enhanced microglial responses, and upregulation of MHC-I and MHC-II expression on the third day of transplantation. But they decreased obviously except Iba-1 positive cells and MHC-II expression. When injection of both mms6-GFP-labeled NSCs and GFP-labeled NSCs aslo induced similar responses as HEK-293T cells on the third days, but MHC-I and MHC-II expression decreased 3 weeks after transplantation. In addition, mms6 transgene-modified NSCs did not produce peripheral splenic response responses as well as astrocytes, miroglial cells, MHC-I and MHC-II positive cells responses when compared with non-modified NSCs. The present study provides preliminary evidence that transgenic modification does not aggravate immunological responses in NSC transplantation.